Waqf Literacy: The Dynamics of Waqf in Indonesia - Ahmad Lukman Nugraha; Adib Susilo; Miftahul Huda; Mohamad Anton Athoillah; Chaerul Rochman (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
In the history of Islamic civilization, waqf has been a pillar of the glory of Islam. The function of waqf is as a provider of public facilities and social facilities that support the life of the Muslim community, such as mosques, squares, Islamic schools, cemeteries and public roads. The development of waqf in Indonesia can have an influence on fiscal policy, namely through cash waqf. Even though Indonesia has a fairly large waqf potential, Indonesia has not been able to manage its waqf properly. Therefore, studies related to the development of waqf in Indonesia are still an interesting study for both scientists and practitioners. The purpose of this article is to review the development of waqf in Indonesia. The approach used in this paper is descriptive qualitative. The author finds the development of waqf in Indonesia is very dynamic. It can be seen from the existing phenomena, the dynamics of the waqf fatwa and the products being donated are increasingly diverse. At first, waqf only wallowed in fixed assets such as land, schools, Islamic boarding schools, and buildings that had a static nature. Beginning with the 2004 waqf law, waqf objects were transformed into cash waqf which were more practical and productive. Followed by the establishment of BWI in the same year by the Government led to an increase in the administrative management of waqf. Dalam sejarah peradaban Islam, wakaf pernah menjadi penopang kegemilangan Islam. Fungsi wakaf sebagai penyedia fasilitas umum dan fasilitas sosial yang menopang kehidupan masyarakat muslim, seperti masjid, lapangan, madrasah, kuburan dan jalan umum. Perkembangan wakaf di Indonesia dapat memberikan pengaruh terhadap kebijakan fiskal yakni melalui wakaf tunai. Meskipun Indonesia memiliki potensi wakaf yang cukup besar, namun Indonesia belum dapat mengelola wakafnya dengan baik, Oleh karena itu kajian terkait perkembangan wakaf di Indonesia masih saja menjadi kajian yang menarik baik di kalangan akademisi maupun praktisi. Tujuan dari artikel ini adalah untuk mengkaji bagaimana perkembangan wakaf di Indonesia. Pendekatan yang digunakan dalam makalah ini ialah kualitatif deskriptif. Penulis menemukan perkembangan wakaf di Indonesia sangat dinamis. Terlihat dari fenomena yang ada, dinamika fatwa wakaf dan pengembangan jenis aset yang diwakafkan semakin beragam. Pada awalnya, wakaf hanya berkubang pada aset tidak bergerak sepeti tanah, sekolah, pesantren, bangunan yang memiliki sifat statis. Diawali dengan undang-undang wakaf tahun 2004, benda wakaf bertransformasi menjadi wakaf tunai yang lebih bersifat praktis dan produktif. Disusul dengan pembentukan BWI pada tahun yang sama oleh Pemerintah menimbulkan peningkatan pengelolaan wakaf secara administratif.